(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
A wide literary tradition narrated by D.S., 4.22.5, tied to musical legends concerning the cicadas on the Alex river, refers to the passage of Heracles across the boundary territory between Rhegion and Locri. The careful reading of the texts, however, induces us to set the known episode about Heracles, disturbed by cicadas while resting, on the northern boundary between the two chorai along the Tyrrhenian side, within the area marked by a strong conflict between the two rival apoikiai. The bronze leaf with the inscription to Heracles Rheginus just comes from this border area of Rhegion chora, inside the district of Metauros river, signed by both indigenous settlements and Locresian claims. The inscription should not be taken as a certain clue for the existence of a sanctuary of the hero, but can represent a clear sign of his strong presence as a cultic reference for the Rheginian scattered through the colonial eschatia. Both analyzing the inscription historical-cultural context of provenance and considering the liminal worshiping places of the heros-theos, linked to the youth rites of passage, we could explain the rise of the dedication referring to the activity of the ephebes garrisoning the colonial chora.